Adjusting the Organization-Managerial Sphere in Conditions of New Scientific and Technological Revolution - V. S. Skrug (Вестник Российского экономического университета имени Г. В. Плеханова)
Setting-up and functioning of state, regional and city bases and banks of data required serious transformation of the whole information sphere. It is necessary to regulate, structure and unify the pattern and content of the principle types of documents and data being collected, to arrange procedures of formation and actualization of data, coordinate the interaction of key data storages. The topicality of the research subject can be explained by the transition stage in scientific and technological development and complicated process of public acceptance of modern drastic innovation. Investigation of interconnection between technical and social progress takes root in works by K. Marx, F. Engels, J. Schumpeter, G. M. Keince. The goal of the research is to study development and perfection of organization-managerial sphere at the stage of new scientific and technological revolution. The author on the basis of collection and summarizing (synthesis), systematization (systematic method) and comparative analysis (complex and comparative and analytical methods) of materials obtained from official information resource and other sources of information analyzes the following aspects of management: organization-structural, functional, informationtechnological and methodological.